ANALISIS KINERJA PEGAWAI DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN JEPARA - Sekti Aji Wibowo; Muhammad Mustam; Retna Hanani (Journal of Public Policy and Management Review, 2013)
This study aims to determine the correlation between employee capability and employee motivation with the performance of employees in the Department of Population and Civil Registration Jepara. The study was conducted with population totaled 27 people.The method of analysis in this study is quantitative data analysis using the Kendall tau_b formula to test the hypothesis. Analysis shows:1. Correlation between employee capability variables with employee performance variable showed a correlation coefficient of 0.243, which means there is a positive relationship but not significant.2. Correlation between the employee motivation variables with employee performance variable showed a correlation coefficient of 0.467, which means there is a positive and significant the correlation.3. Employee capability variable and employee motivation variable interrelate together with employee performance variables. This is seen from the results of correlation and cross table that shows the results of a positive correlation between the employee capability variables and employee motivation variables with the employee performance variable.